Membangun Karakter Generasi Digital Melalui Literasi Digital Perspektif Pendidikan Islam - Hasanah, Uswatun; Prasasti, Eka Putri; Febriani, Evi; Hasanah, Ida Faridatul (Universitas Muhammadiyah Makassar, 2024)
This research aims to describe the optimization of digital literacy as an effort to build the character of the digital generation in line with values in Islamic education. The study employs a qualitative approach with a literature review method. Data were collected from various references related to the digital generation, digital literacy, character education, and Islamic education. The findings indicate that optimizing digital literacy integrated with Islamic character education values has significant potential in cultivating the character of the digital generation to be wise and ethical in utilizing technology and digital information. The implementation of digital literacy strategies in online learning, parental supervision, and social media campaigns is key to the success of character building for the digital generation in the current all-digital era. This research is expected to provide theoretical and practical contributions to educators, parents, and policymakers in building the character of the Indonesian digital generation, aiming for them to grow into a resilient and morally upright golden generation in 2045.